Rare copy number variants in individuals at clinical high risk for psychosis: Enrichment of synaptic/brain‐related functional pathways. Issue 2 (19th November 2019) - Jagannath, Vinita; Grünblatt, Edna; Theodoridou, Anastasia; Oneda, Beatrice; Roth, Alexander; Gerstenberg, Miriam; Franscini, Maurizia; Traber‐Walker, Nina; Correll, Christoph U.; Heekeren, Karsten; Rössler, Wulf; Rauch, Anita; et al.
Abstract: Schizophrenia is a complex and chronic neuropsychiatric disorder, with a heritability of around 60–80%. Large (>100 kb) rare (<1%) copy number variants (CNVs) occur more frequently in schizophrenia patients compared to controls. Currently, there are no studies reporting genome‐wide CNVs in clinical high risk for psychosis (CHR‐P) individuals. The aim of this study was to investigate the role of rare genome‐wide CNVs in 84 CHR‐P individuals and 124 presumably healthy controls. There were no significant differences in all rare CNV frequencies and sizes between CHR‐P individuals and controls. However, brain‐related CNVs and brain‐related deletions were significantly more frequent in CHR‐P individuals than controls. In CHR‐P individuals, significant associations were found between brain‐related CNV carriers and attenuated positive symptoms syndrome or cognitive disturbances (OR = 3.07, p = .0286). Brain‐related CNV carriers experienced significantly higher negative symptoms ( p = .0047), higher depressive symptoms ( p = .0175), and higher disturbances of self and surroundings ( p = .0029) than noncarriers. Furthermore, enrichment analysis of genes was performed in the regions of rare CNVs using three independent methods, which confirmed significant clustering of predefined genes involved in synaptic/brain‐related functional pathways in CHR‐P individuals. These results suggest that rare CNVs might affect synaptic/brain‐related functional pathways in CHR‐P individuals.